System dynamics: an approach to modeling supply chain performance measurement - Liu, Peide; Atifeh, Morteza; Khorshidnia, Mohsen; Taheri, Seyed Ghiasuddin (Technological and Economic Development of Economy, 2023)
The complexity of goods and services in the current world has caused individual companies that do not have the help and cooperation of other organizations to face many problems for their survival. In this paper, a system dynamics model was proposed by creating a cause-effect curve to increase supply chain (SC) performance with an emphasis on agility and flexibility (AAF) indicators. The proposed model aimed to reduce cost and delivery time and increase customer satisfaction by considering AAF indicators. To this end, the concepts used were first introduced. Afterward, the important goals were identified by reviewing the existing literatures and interviewing experts in the field of AAF indicators in the studied SC. In the next step, the model was constructed by determining the cause-and-effect (CAE) relationships between the variables. Finally, by developing and simulating different scenarios, the results showed that AAF alone and absolutely cannot enhance profitability. By implication, to increase profitability, AAF do not need to be enhanced to the highest level, but an optimal point must be found. Finally, an optimal level of AAF was estimated. by using this system and considering that this system supports the production line, the ability to respond to sudden demands is increased and as a result, the speed of covering these demands increases.